Decision-making by the administrative bodies of sports clubs participating in the Iraqi Premier League for football for the 2022-2023 season. - hashim, ahmed; Yousif , Tariq (Journal of Physical Education, 2024)
The research aimed to study the decision-making of the administrative bodies of sports clubs participating in the Iraqi Football Premier League for the 2022-2023 season. The researchers used the descriptive approach (survey study) to suit the nature of the research. The research community is represented by members of the administrative bodies of the sports clubs participating in the Iraqi Premier Football League for the 2022-2023 season, who number (177) members of the administrative body. The researchers used the questionnaire to collect the necessary data to achieve the goal of researching The method of applying a questionnaire aimed to identify the decision-making of the administrative bodies of sports clubs. The most important results reached by the researchers were that the level of decision-making of the administrative bodies of sports clubs in the Premier League in football was at a low level. The degree of effectiveness of decision-making by the administrative bodies of sports clubs in the Premier League in football, according to the scale magazines, was collecting data and information first, then identifying the problem, followed by choosing the appropriate alternative to solve the problem at a low level, then following up on the implementation of the decision and evaluating it, and finally identifying the available alternatives and evaluating them at a very low level.